2017
DOI: 10.1111/jocd.12312
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of hair removal efficacy and side effect of neodymium:Yttrium‐aluminum‐garnet laser and intense pulsed light systems (18‐month follow‐up)

Abstract: Unwanted hair can be reduced by both systems safely and effectively; however, IPL has less side effects and higher satisfaction scores.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 27 publications
0
3
3
Order By: Relevance
“…All studies comparing IPL and Nd:YAG systems in terms of pain have used therapies for purposes of epilation. However, since the systems used differ, it is not possible to perform any direct comparison between them, although, in contrast to our findings, studies have generally reported that IPL systems caused less pain than Nd:YAG procedures [37][38][39][40][41] . Goh CL reported that patients described a prolonged burning sensation with the IPL system, but a transient stinging sensation with Nd:YAG 41 .…”
Section: Discussioncontrasting
confidence: 99%
“…All studies comparing IPL and Nd:YAG systems in terms of pain have used therapies for purposes of epilation. However, since the systems used differ, it is not possible to perform any direct comparison between them, although, in contrast to our findings, studies have generally reported that IPL systems caused less pain than Nd:YAG procedures [37][38][39][40][41] . Goh CL reported that patients described a prolonged burning sensation with the IPL system, but a transient stinging sensation with Nd:YAG 41 .…”
Section: Discussioncontrasting
confidence: 99%
“…All studies comparing IPL and Nd:YAG systems in terms of pain have used therapies for purposes of epilation. However, since the systems used differ it is not possible to perform any direct comparison between them, although, in contrast to our findings, studies have generally reported that IPL systems cause less pain than Nd:YAG procedures [37][38][39][40][41] . Goh CL reported that patients described a prolonged burning sensation with the IPL system, but a transient stinging sensation with Nd:YAG 41 .…”
Section: Discussioncontrasting
confidence: 99%
“…The theory states that the pulse duration should be equal or shorter to the thermal relaxation time (TRT) of the hair shaft in order to be effective in hair follicle destruction. The TRT of the hair shaft is estimated to be between 10 and 100 ms 11,12 so, the most commonly used Nd:YAG hair removal pulse duration ranges between 15 and 50 ms with fluences between 25 and 70 J/cm 2 using 6–20 mm spot size 3,7,13–15 . Recent studies showed that shorter Nd:YAG pulses with pulse width of 0.6–3.5 ms are also effective in hair reduction, while maintaining better comfort for the patient.…”
Section: Introductionmentioning
confidence: 99%
“…The TRT of the hair shaft is estimated to be between 10 and 100 ms 11,12 so, the most commonly used Nd:YAG hair removal pulse duration ranges between 15 and 50 ms with fluences between 25 and 70 J/cm 2 using 6-20 mm spot size. 3,7,[13][14][15] Recent studies showed that shorter Nd:YAG pulses with pulse width of 0.6-3.5 ms are also effective in hair reduction, while maintaining better comfort for the patient. This can be attributed to higher peak power when shorter pulse are used.…”
mentioning
confidence: 99%